Surveillance as a safe and effective option for treatment of stage I seminoma - Quaresma, Vasco; Henriques, Diogo; Marconi, Lorenzo; Lorigo, João; Ferreira, Ana-Marta; Jarimba, Roberto; Nunes, Pedro; Figueiredo, Arnaldo; Parada, Belmiro (Archivio Italiano di Urologia e Andrologia, 2023)
Introdubction: Stage I seminoma has a very good prognosis, yet approximately 15% have subclinical metastatic disease and will relapse after orchidectomy alone. Several management approaches have been investigated. We aimed to evaluate the clinical outcomes of real-world patients with stage I seminoma, analysing prognostic factors influencing treatment choice and oncological outcomes. Methods: Retrospective, single institution study, with 55 patients diagnosed with clinical stage I seminoma between 2007 and 2020. Selected patients were analysed regarding three management approaches - surveillance, adjuvant radiotherapy and adjuvant carboplatin AUC7. Overall survival and progression-free survival outcomes were analysed. Predictors of treatment choice were determined, and predictors of recurrence were analysed in patients on active surveillance. Results: The median follow-up time was 91 months (13-165). Overall survival at 10 years was 98.2%. Stage I seminoma patients had a 1-, 3- and 10-year progression free survival of 98%, 94% and 89%, respectively. Three-year progression free survival was 92.0% for those on active surveillance (IC95%, 91.5-92.5%), 95.2% for carboplatin (IC95%, 94.8-95.6%) and 100% for those on adjuvant radiotherapy (p > 0.05). All relapses on active surveillance protocols occurred during the first 24 months. Overall, 43% of patients who underwent adjuvant treatment reported adverse effects of therapy, with higher incidence on radiotherapy group (63%). Conclusions: Stage I seminoma have excellent prognosis, high cure rates, and low treatment-associated morbidity. Active surveillance is a safe modality when applied to selected patients. Adjuvant radiotherapy and adjuvant chemotherapy with carboplatin show similar results, with fewer adverse effects on chemotherapy arm.